International Technology Spillovers in Climate-Economy Models: Two Possible Approaches - Enrica De Cian (Fondazione Eni Enrico Mattei (FEEM), 2006)
This paper analyzes two possible methodologies of modeling international technology spillovers in a climate-economy CGE model. Technological change, by affecting productivity, energy and carbon intensity, eventually influences the amount of CO2 emissions, the costs and the timing of the policies targeted at their reduction. Technological change is here defined so as to include also the diffusion and adoption phase. In an increasingly integrated world, new products and technologies developed in one region will eventually diffuse internationally. The two approaches described in this paper are based on two mechanisms used to model technological change in climate models: learning curves, total factor productivity and the autonomous energy efficient improvement parameter. This paper considers spillovers mediated by international trade in capital goods. In particular, it looks at how imports machinery and equipments from the OECD countries can affect the technology variables related to CO2 emissions: learning rates in the first approach, productivity, energy and carbon intensity in the second one.
Keywords: F18; O33; Q54; Q55; 330; Climate Policy; International Trade; Learning Curves; International Technology Spillovers; Biased Technical Change